Wysokość siedmioletnich odnowień dębowych na gniazdach w różnych warunkach siedliskowych - Bolibok, Leszek; Andrzejczyk, Tadeusz; Drozdowski, Stanisław; Szeligowski, Henryk (Leśne Prace Badawcze, 2011)
Spatial variability in the height of planted oak saplings was investigated at three different sites: deciduous, mixed deciduous and mixed coniferous forest types in artificial gaps of size about 15 and 23 ares (1 are = 100 m -2 ). (four gaps for 'gap size – forest site’ combination). The height of planted trees was measured on five circular plots (radius 3 m) placed in the gap centre and 9 meters from southern, northern, eastern and western gap borders. At the deciduous forest site, the tallest 7-year-old oaks were growing in the northern part of the gaps and oak height diminished towards the south. The opposite growth pattern was observed in the remaining forest sites. The water holding capacity of rich soils is usually greater than that of poor soils, and we attribute the observed trends to good water supplies for young oaks allowing them to grow better on the northern side of gaps where they receive more light; whereas on poor soils moisture is more important. There was no biologically significant difference between the heights of oaks in gaps of 15 ares and gaps of 23 ares at the mixed deciduous forest site. This suggests that it may be possible for foresters to cut larger gaps while still promoting regeneration without a loss in productivity.